Changes in Seasonal Respiratory Illnesses in the United States During the Coronavirus Disease 2019 (COVID-19) Pandemic. (29th April 2021) - Rodgers, Loren; Sheppard, Michael; Smith, Amanda; Dietz, Stephanie; Jayanthi, Praveena; Yuan, Yan; Bull, Lara; Wotiz, Samantha; Schwarze, Tessa; Azondekon, Roseric; Hartnett, Kathleen; Adjemian, Jennifer; et al.
Abstract: Background: Respiratory tract infections are common, often seasonal, and caused by multiple pathogens. We assessed whether seasonal respiratory illness patterns changed during the COVID-19 pandemic. Methods: We categorized emergency department (ED) visits reported to the National Syndromic Surveillance Program according to chief complaints and diagnosis codes, excluding visits with diagnosed SARS-CoV-2 infections. For each week during 1 March 2020 through 26 December 2020 ("pandemic period"), we compared the proportion of ED visits in each respiratory category with the proportion of visits in that category during the corresponding weeks of 2017–2019 ("pre–pandemic period"). We analyzed positivity of respiratory viral tests from 2 independent clinical laboratories. Results: During March 2020, cough, shortness of breath, and influenza-like illness accounted for twice as many ED visits compared with the pre–pandemic period. During the last 4 months of 2020, all respiratory conditions, except shortness of breath, accounted for a smaller proportion of ED visits than during the pre–pandemic period. Percent positivity for influenza virus, respiratory syncytial virus, human parainfluenza virus, adenoviruses, and human metapneumovirus was lower in 2020 than 2019. Although test volume decreased, percent positivity was higher for rhinovirus/enterovirus during the final weeks of 2020 compared with 2019, with ED visits similar to the pre–pandemic period. Conclusions: Broad reductions in respiratory test positivity and respiratory ED visits (excluding COVID-19) occurred during 2020. Interventions for mitigating spread of SARS-CoV-2 likely also reduced transmission of other pathogens. Timely surveillance is needed to understand community health threats, particularly when current trends deviate from seasonal norms.